PERTINGKATAN KEBUTUHAN DALAM MAQASID ASY-SYARIAH (Perspektif Ilmu Ekonomi Islam Kontemporer) - Waryani Fajar Riyanto (Jurnal Hukum Islam, 2010)
One of the basic methods in development of Islamic law which has muamalah (Islamic Economics) as a playing field is maqashid asy-syari’ah. The main goal of syariah is to generate and create maslahah, whereas the purpose of muamalah is to meet human needs. This article represents a preliminary study in attempting to find a point of contact of those two maslahah viewed from the steps of human needs as homo-economicus/homo-Islamicus.